UJI BEBERAPA DOSIS BIOFUNGISIDA BERBAHAN AKTIF Trichoderma koningii Rifai TERHADAP PENYAKIT VIRUS KOMPLEKS, PERTUMBUHAN DAN PRODUKSI CABAI MERAH (Capsicum annuum L.) - Sartika Sartika; Muhammad Ali; Yetti Elfina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
One of the disease that can significatly decrease the red chili productivity is virus complex. The disease can be controlled by the utilization of microorganism such as Trichoderma koningii Rifai formulated in a biofungicide. The dose of biofungicide given to the plants can determine the effect of virus complex disease. The research aims to obtain the best dose of biofungicide of T. koningii to increase the resistance of red chili to virus komplex and to study its effect on the growth and yield of the red chili. This research has been conducted at Plant Pathology Laboratory and Agribusiness Incubator Green House, Agriculture Faculty of Riau University from October 2015 to February 2016. The research was carried out experimentally using a completely randomized design consisted of 5 doses (0, 25, 50, 75 dan 100 g/polybag) and 3 replication. Data obtained were statistically analyzed using analysis of variance and continued with Duncan’s New Multiple Range Test (DNMRT) at 5% level. The result showed that the virus complex infection in red chili which were applied with some doses of biofungicide of T. koningii had different effect on the first time of symptom appeared, disease intensity, plant growth and yield. Biofungicide of T. koningii at 100 g/polybag can increase the resistance of red chili and the growth and production. Keywords: Biofungicide, Trichoderma koningii, virus complex, red chili